2006
DOI: 10.1590/s0100-204x2006000200008
|View full text |Cite
|
Sign up to set email alerts
|

Deficit hídrico e produtividade na cultura do milho

Abstract: Resumo -O objetivo deste trabalho foi avaliar o impacto do deficit hídrico, no rendimento de grãos de milho, e a eficácia da irrigação em todo ciclo e, especificamente, no florescimento. Os dados foram obtidos em dez anos de experimentação, durante os quais doses variáveis de irrigação foram aplicadas por um sistema de aspersão, localizado no centro da área experimental. Foram calculados balanços hídricos, tendo como variáveis a água precipitada (chuva e irrigação) e a evapotranspiração máxima do milho. Foram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
37

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 5 publications
3
32
0
37
Order By: Relevance
“…Standardized anomalies were calculated by dividing each value by the standard deviation in the time-series. and the atmospheric evaporative demand are high (Bergamaschi et al, 2001(Bergamaschi et al, , 2006Radin et al, 2003). Tasseling occurred between December and January (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Standardized anomalies were calculated by dividing each value by the standard deviation in the time-series. and the atmospheric evaporative demand are high (Bergamaschi et al, 2001(Bergamaschi et al, , 2006Radin et al, 2003). Tasseling occurred between December and January (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The average sowing date for each municipality, obtained from the data of the official extension service in the state (Emater, RS), represents the average date by which at least 50% of the maize crops were sown between 2002 and 2005. Once the sowing data was known, the mean date of tasseling, milky and physiological maturity was obtained from a set of experimental data (Matzenauer et al, 1995;Bergamaschi et al, 2006) for short season maize hybrids (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, supplementary water was emphasized as one of the techniques necessary to stabilize the production of maize (MINUZZI; RIBEIRO, 2012). Bergamaschi et al (2006) observed, from a ten-year field experiment in the city of Eldorado do Sul, RS, that total irrigation provided an increase of nearly 70% in maize yield compared with non-irrigated crops. Moreover, Vieira et al (2013) also found a significant increase in irrigated crops compared with non-irrigated plants.…”
Section: Introductionmentioning
confidence: 99%